HUBUNGAN ANTARA KEJADIAN KOMPLIKASI DENGAN KUALITAS HIDUP PENDERITA DIABETES MELLITUS TIPE 2 PADA PASIEN PROLANIS DI WILAYAH KERJA PUSKESMAS DANDER - ferawati, ferawati; Hadi Sulistyo, Angger Anugerah (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
The number of patients who suffers with is increasing every year. Poor management of DM can cause various complications. DM complications are one of the factors that can affect quality of life. A decrease in quality of life in patients with type 2 diabetes can significantly affect the morbidity, mortality, and life expectancy of patients. The purpose of this study was to determine the relationship between the incidences of DM’s complications with quality of life in patients with DM. This study used the accidental sampling technique in the sample selection method. A total of 30 respondents were involved in this study. Data collection was done by checking the complication data. As for the quality of life data, researchers used the SF-36 questionnaire. Based on the results of the study found 83.3% of respondents had complications of hyperglycaemia. Meanwhile, 56.7% of respondents have a poor quality of life. Pearson correlation was used in this study to analyze the relationship between the two variables. The results of the correlation test found a strong relationship between complications and quality of life of patients (p = .00). This study shows that participants have high rates of complications with poor quality of life. Further research regarding nursing interventions to reduce the number of complications is needed in the same location setting.Keywords: Diabetes Mellitus, Complications, Quality of Life